Utilization and Challenges of Mobile learning (m-Learning) in Medical Education – Insights from MBBS Students - Ansar, Abdul; Chaturvedi, Ruchi; Ahmad, Sumaiya; Zaidi, Zeashan H (Indian Journal of Community Health, 2025)
Background: The National Medical Commission’s (NMC) competency based medical education (CBME) curriculum places a strong emphasis on lifelong learning and self-directed study. Mobile learning provides the adaptability and accessibility needed to facilitate these learner centred strategies This study explores MBBS students’ usage patterns and challenges associated with Mobile learning. Methodology: A pre-tested, self-administered questionnaire was used to collect data .400 MBBS students from different academic phases participated in a descriptive cross-sectional study. Convenience sampling was used. SPSS software version 22 was used for the analysis. Results :60% of respondents were female, and the majority (66.5%) were between the ages of 21 and 23. 92.5% of students were aware of m-learning apps, and 62.2% of them used them frequently throughout the day. Only 21.5% of respondents said they primarily used mobile for educational purposes, despite 88% agreeing that it had a positive impact on learning. Practical sessions ranked highest among preferred learning methods. Distractions (35.5%), internet dependence (21.5%), and decreased practical exposure (55.2%) were the main challenges faced by MBBS students during m learning. Conclusion: Traditional and hands-on learning approaches continue to be the most popular, despite the fact that m-Learning is well-liked by MBBS students. By combining m-Learning with didactic and practical elements, a blended approach can overcome technological obstacles and maximize educational effectiveness.